Pengaruh Komunikasi Terapeutik Melalui Edukasi Terapi Seni Terhadap Konsep Diri Remaja - Rotua Suriany Simamora; Nurhidayah Amir; Lisna Agustina; Lisna Nuryanti; Arabta M Peraten; Roulita Roulita; Andi Pranata (SEHATI: Jurnal Kesehatan, 2025)
Adolescence is a time full of color and dynamics, and it also has many emotional upheavals that mark a person's journey towards adulthood. During adolescence, a person renews his or her identity that has existed since birth and faces many challenges. they experience physical, social, intellectual, and emotional changes. The aim of the research carried out was to determine the influence of therapeutic communication through art therapy on adolescents' self-concept. Method uses the research design used in this research is quantitative research with a quasi-experiment design using a one group pre-test post test approach. Based on statistical analysis with a significance level of 95% or an α value of 5% (0.05), it was obtained that p value (0.965) more than α value (0.05) so it can be concluded that the result H0 is accepted which means there is no difference in self-concept before and after therapeutic communication was carried out through art therapy for teenagers at SMPN 50 Bekasi City. The results of the research did not show any significant differences. This shows that there is difference before and after therapeutic communication through art therapy. This shows that in the context of the adolescent population at SMPN 50 Bekasi City, art therapy does have a strong enough impact to significantly influence self-concept